Open Trip and Backpacker Tourism Trends in the Digital Era: A Review of the Literature and Implications for Travel Businesses - Rahjasa, Putu Surya Laksana (International Journal Labs, 2025)
The emergence of digital technology and social media has fundamentally changed the landscape of the tourism industry, particularly in facilitating community-based collective travel practices such as open trips and backpacker tourism. This study aims to map the latest trends, characteristics of tourists, and business implications of this phenomenon through a scoping review approach based on the PRISMA-ScR framework. A total of 30 internationally indexed scientific articles (2020–2024) were systematically analyzed to explore the interaction between digital communities, online travel platforms, and the influence of travel influencers on the behavior of Millennial and Gen Z travelers. and open. On the other hand, the existence of conventional travel agents faces the challenge of disintermediation, but at the same time opens up opportunities for strategic collaboration with online communities and micro-influencers to develop narrative-based and community-based tour packages. The results of the research provide a conceptual contribution to the digital tourism literature and offer practical implications for industry players to adopt hybrid business models that are adaptive, inclusive, and relevant to today's digital tourism dynamics. Advanced research suggestions include an in-depth exploration of community business model design as well as the integration of artificial intelligence in personalized travel planning and recommendations.